RF MEMS Switches and Integrated Switching Circuits - Liu, Ai-Qun.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Microelectromechanical Systems (MEMS) stand poised for the next major breakthrough in the silicon revolution that began with the transistor in the 1960s and has revolutionized microelectronics. MEMS allow one to not only observe and process information of all types from small scale systems, but also to affect changes in systems and the environment at that scale. “RF MEMS Switches and Integrated Switching Circuits” builds on the extensive body of literature that exists in research papers on analytical and numerical modeling and design based on RF MEMS switches and micromachined switching circuits, and presents a unified framework of coverage. This volume includes, but is not limited to, RF MEMS approaches, developments from RF MEMS switches to RF switching circuits, and MEMS switch components in circuit systems. This book also: -Presents RF Switches and switching circuit MEMS devices in a unified framework covering all aspects of engineering innovation, design, modeling, fabrication, control and experimental implementation -Discusses RF switch devices in detail, with both system and component-level circuit integration using micro- and nano-fabrication techniques -Includes an emphasis on design innovation and experimental relevance rather than basic electromagnetic theory and device physics “RF MEMS Switches and Integrated Switching Circuits” is perfect for engineers, researchers and students working in the fields of MEMS, circuits and systems and RFs.
Lateral Series Switches -- Capacitive Shunt Switches -- Coplanar Waveguide Transmission Line -- Single-Pole-Multi-Throw Switching Circuits -- Tunable Electromagnetic Band Gap Bandstop Filter -- Tunable Electromagnetic Bandpass Filter and Reconfigurable Circuit -- Capacitive Switching Bandpass Filters -- Substrate Transfer Process -- Surface Planarization Process.
Keywords: Electronic circuits; Mechanical engineering; Electronics; Microelectronics; Circuits and Systems; Mechanical Engineering; Electronics and Microelectronics, Instrumentation